Parenting Menumbuhkembangkan Kemampuan Anak Usia Dini dalam Bingkai Pendidikan Karakter - Zulkifli Lessy; Devi Permatasari; Ahmad Kamal Assidiqi; Hasriyah F; Tiara Nur Urbiyanti (Indonesian Journal of Elementary and Childhood Education, 2022)
Parents need to be aware of the development of their child's every step. But many parents are indifferent to it. They now actually give their love through babysitter and choose to become a career woman or a business father. So that when there is no other way to calm the baby, instead give a gadget hoping that the baby's crying will stop. On the one hand, it causes addiction, and some adverse effects affect the development and growth of the child. It really depends on what your parents accept and obey. To explore the responsibilities and roles of parents, the concept we know today is called parenting. This study uses an exploratory case study technique for qualitative research, and this study uses a qualitative case study technique. The primary data collection method consists of a literature review and secondary data obtained from the internet in the form of public data such as journals and articles.